2019
DOI: 10.1371/journal.pbio.3000154
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase beta is the master regulator of cAMP signalling during malaria parasite invasion

Abstract: Cyclic nucleotide signalling is a major regulator of malaria parasite differentiation. Phosphodiesterase (PDE) enzymes are known to control cyclic GMP (cGMP) levels in the parasite, but the mechanisms by which cyclic AMP (cAMP) is regulated remain enigmatic. Here, we demonstrate that Plasmodium falciparum phosphodiesterase β (PDEβ) hydrolyses both cAMP and cGMP and is essential for blood stage viability. Conditional gene disruption causes a profound reduction in invasion of erythrocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 59 publications
8
70
0
Order By: Relevance
“…Conditional ablation of PDEβ led to a 70% reduction in invasion and increased phosphorylation of over 230 parasite protein phosphosites, most of which contained a minimal PKA consensus motif (R/K, x, pS/pT), suggesting that the PDEβ knockout phenotype resulted from inappropriate hyper-activation of PKA due to uncontrolled cAMP levels. Of note, phosphorylation of AMA1 Ser 610 was up-regulated in the PDEβ null mutant, further supporting the notion that it is a PKA substrate [25]. In the present study, we have examined the role of cAMP signalling in P .…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…Conditional ablation of PDEβ led to a 70% reduction in invasion and increased phosphorylation of over 230 parasite protein phosphosites, most of which contained a minimal PKA consensus motif (R/K, x, pS/pT), suggesting that the PDEβ knockout phenotype resulted from inappropriate hyper-activation of PKA due to uncontrolled cAMP levels. Of note, phosphorylation of AMA1 Ser 610 was up-regulated in the PDEβ null mutant, further supporting the notion that it is a PKA substrate [25]. In the present study, we have examined the role of cAMP signalling in P .…”
Section: Introductionsupporting
confidence: 80%
“…Consistent with this, motif analysis showed that the phosphorylation sites fit a PKA consensus and closely resemble those identified in a recent study of sites enriched in a P . falciparum PDEβ knockout in which PKA activity was enhanced due to raised cAMP levels [25] (S2C Fig and S2D Fig). A total of 77 sites that we identified as being significantly hypophosphorylated in both the ACβ- and PKA-deficient parasites were also quantified in the recent PDEβ-dependent phosphoproteome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[46,47] (data available in PlasmoDB) indicated that PF3D7_0507400 is transcribed in asexual blood stages, with peak expression in mature schizonts. To evaluate expression at the protein level we examined a recently obtained global proteomic dataset [48]. This clearly identified with high confidence two tryptic peptides of SUB1-ProM (corresponding to 17.6% coverage) in extracts of P. falciparum asexual blood stage schizonts (Supplementary Figure S3), confirming that the protein is expressed in these clinically relevant developmental stages of the parasite lifecycle.…”
Section: Sub1-prom Is Expressed In Asexual Blood Stages Of P Falciparummentioning
confidence: 74%
“…Synchronized cultures are of great value in the study of many processes in the asexual cycle and the ability to synchronize egress and invasion to within minutes will allow the investigation of these rapid processes on different scales, allowing for a wide range of studies, including large-scale biochemical investigation of proteins involved, such as the proteolysis of MSP1 and AMA1 proteins [54-56]. Furthermore, as it makes timing of egress and invasion very predictable, this method will greatly aid the imaging of egress and invasion by video microscopy.…”
Section: Discussionmentioning
confidence: 99%